Lymphatic Transport of Drugs after Intestinal Absorption: Impact of Drug Formulation and Physicochemical Properties - Ryšánek, Pavel; Grus, Tomáš; Šíma, Martin; Slanař, Ondřej (Pharmaceutical research, 2020)
PURPOSE: To provide a comprehensive and up-to-date overview focusing on the extent of lymphatic transport of drugs following intestinal absorption and to summarize available data on the impact of molecular weight, lipophilicity, formulation and prandial state. METHODS: Literature was searched for in vivo studies quantifying extent of lymphatic transport of drugs after enteral dosing. Pharmacokinetic data were extracted and summarized. Influence of molecular weight, log P, formulation and prandial state was analyzed using relative bioavailability via lymph (FRL) as the parameter for comparison. The methods and animal models used in the studies were also summarized. RESULTS: Pharmacokinetic data on lymphatic transport were available for 103 drugs. Significantly higher FRL [median (IQR)] was observed in advanced lipid based formulations [54.4% (52.0)] and oil solutions [38.9% (60.8)] compared to simple formulations [2.0% (27.1)], p < 0.0001 and p = 0.004, respectively. Advanced lipid based formulations also provided substantial FRL in drugs with log P < 5, which was not observed in simple formulations and oil solutions. No relation was found between FRL and molecular weight. There were 10 distinct methods used for in vivo testing of lymphatic transport after intestinal absorption so far. CONCLUSION: Advanced lipid based formulations provide superior ability to increase lymphatic absorption in drugs of various molecular weights and in drugs with moderate to low lipophilicity.
Keywords: modely u zvířat; lidé; intestinální absorpce; Drug Compounding; farmakokinetika; biologická dostupnost; léčivé přípravky; příprava léků; aplikace orální; lékové transportní systémy; Databases, Bibliographic; Drug Delivery Systems; Humans; Pharmacokinetics; Biological Transport; Models, Animal; Administration, Oral; zvířata; databáze bibliografické; Animals; lymfatický systém; biologický transport; Intestinal Absorption; Lymphatic System; Pharmaceutical Preparations; Biological Availability